2009
DOI: 10.1177/030802260907200803
|View full text |Cite
|
Sign up to set email alerts
|

Home and Clinical Assessments of Instrumental Activities of Daily Living: What Could Explain the Difference between Settings in Frail Older Adults, If Any?

Abstract: Background: Older patients are usually assessed by occupational therapists in hospital before going home. However, for many frail older adults, this assessment in an unfamiliar environment might not be as representative of their functional abilities as an assessment at home. The aim of this literature review was to determine if differences exist between home and clinical instrumental activities of daily living (IADL) assessments of frail older adults and identify factors that might explain those differences, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Consistent with this account, there is in fact evidence that human residents are able to engage more efficiently in a variety of behaviors because of their greater awareness of the environmental invariants specific to the setting. For example, assessments of elderly and disabled adults' motor skills (i.e., ability to interact with and move around the environment) and process skills (i.e., ability to carry out actions/ steps and modify performance) have been found to be greater when measured in their home, relative to clinical settings (Hoppes, Davis, & Thompson, 2003;Provencher, Demers, Gagnon, & Gélinas, 2012;Provencher, Demers, & Gélinas, 2009;Raina, Rogers, & Holm, 2007). Tellingly, these improvements appear to be particularly substantial for those with impaired executive functioning (Provencher et al, 2012), who most benefit from having this existing history of behavior within the environment.…”
Section: Individual Differences In Behavior Within Territoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this account, there is in fact evidence that human residents are able to engage more efficiently in a variety of behaviors because of their greater awareness of the environmental invariants specific to the setting. For example, assessments of elderly and disabled adults' motor skills (i.e., ability to interact with and move around the environment) and process skills (i.e., ability to carry out actions/ steps and modify performance) have been found to be greater when measured in their home, relative to clinical settings (Hoppes, Davis, & Thompson, 2003;Provencher, Demers, Gagnon, & Gélinas, 2012;Provencher, Demers, & Gélinas, 2009;Raina, Rogers, & Holm, 2007). Tellingly, these improvements appear to be particularly substantial for those with impaired executive functioning (Provencher et al, 2012), who most benefit from having this existing history of behavior within the environment.…”
Section: Individual Differences In Behavior Within Territoriesmentioning
confidence: 99%
“…Based on these criteria, territories are quite likely to require minimal directed attention to function effectively, yet nevertheless capable of eliciting soft involuntary attention. A behavioral history in the setting provides residents with knowledge of its invariant structure and behavioral opportunities, a fact that eases motor and process skills (Hoppes et al, 2003;Provencher et al, 2012;Provencher et al, 2009;Raina et al, 2007). Because of past behavior physically and perceptually exploring the space, residents will be able to regulate themselves in it with little need for concerted attentional effort.…”
Section: The Design Of Territories To Facilitate Certain Psychologicamentioning
confidence: 99%
“…However, little is known about the characteristics of participants who showed a significant difference between home and clinic environments. A literature review (10) suggested that lower levels of education, poorer balance, reduced grip strength, decline in vision, decreased cognitive resources (such as executive and memory functions), and higher levels of anxiety may predispose frail older adults to have a better performance in a more familiar and predictable environment. However, some of those factors may also increase the risk of falls and injury in the home environment, which is often more crowded and cluttered.…”
Section: Introductionmentioning
confidence: 99%
“…Time spent in an environment tends to support task performance because of greater familiarity with tools and appliances (Provencher et al, 2009), whereas similarity between settings may favor application of knowledge in an unfamiliar context (Barnett and Ceci, 2002). Time spent in an environment tends to support task performance because of greater familiarity with tools and appliances (Provencher et al, 2009), whereas similarity between settings may favor application of knowledge in an unfamiliar context (Barnett and Ceci, 2002).…”
Section: Introductionmentioning
confidence: 99%